Authenticity, Self-Invention and the Power of Storytelling: Sam Shepard’s Postmillennial Work - Mirowska, Paulina (Analyses/Rereadings/Theories: A Journal Devoted to Literature, Film and Theatre, 2020)
The article reflects upon Sam Shepard’s playwrighting in the opening decades of the twenty-first century, paying particular attention to his last play, A Particle of Dread (Oedipus Variations), written specifically for the Derry/Londonderry City of Culture celebrations in 2013, and originally produced by the renowned Field Day Theatre Company. The article seeks to offer an insight into Shepard’s mature multilayered text, which, in many respects, looks back upon almost fifty years of his artistic creativity and, at the same time, expands his vision. It also addresses the realisation of Shepard’s play in performance and the significance of his text in an interplay of multiple creative inputs involved in the production process. While revisiting the familiar landscapes and themes, Shepard’s most recent work negotiates the boundaries between the actual and the fictitious, raising debates about the persistence of myths, mortality and the haunting legacies of the past. Richly intertextual and conspicuously metatheatrical, it grapples with questions of authenticity, performativity and storytelling – the narratives that are passed down, and how they form and inform our lives. It also engages with, and further problematises, issues of personal and cultural identity, which constitute Shepard’s most durable thematic threads, revealing both the dramatist’s acute concern with fateful determinism and commitment to self-invention. Significantly, while Shepard’s postmillennial output highlights the author’s ongoing preoccupation with instability and frontiers of various sorts (from those topographic, temporal and sociopolitical to those of language and art), it equally intimates his attentiveness to correspondences between times, lands and cultures.